2020
DOI: 10.1371/journal.pone.0240367
|View full text |Cite
|
Sign up to set email alerts
|

The effects of video racing games on risk-taking in consideration of the game experience

Abstract: In the present study, we attempted to investigate whether it is the game experience that underlies processes leading to increased risk-taking while playing video racing games (VRGs). The aim of the study was to examine the indirect effect of playing VRGs on risky driving behaviour through various dimensions of the game experience. Thus, we examined the subjective experience of participants playing various VRGs and questioned whether this influenced subsequent driving behaviour. The results of the present study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Asking undergraduates to play video games for 30 minutes, Buelow et al (2015) observed an increase in some executive functions but no increase in risk-taking behavior in the BART. Other researchers observed an association between a history of playing reckless-driving or other risk-glorifying games and risky driving (e.g., Fischer et al, 2007;Stollberg & Lange, 2020) or risky behaviors such as smoking, aggression, or delinquency (e.g., Hull et al, 2014), respectively. However, some of these findings are disputed (see Hilgard et al, 2019;Drummond et al, 2021).…”
Section: The Special Case Of Esportsmentioning
confidence: 99%
“…Asking undergraduates to play video games for 30 minutes, Buelow et al (2015) observed an increase in some executive functions but no increase in risk-taking behavior in the BART. Other researchers observed an association between a history of playing reckless-driving or other risk-glorifying games and risky driving (e.g., Fischer et al, 2007;Stollberg & Lange, 2020) or risky behaviors such as smoking, aggression, or delinquency (e.g., Hull et al, 2014), respectively. However, some of these findings are disputed (see Hilgard et al, 2019;Drummond et al, 2021).…”
Section: The Special Case Of Esportsmentioning
confidence: 99%
“…Asking undergraduates to play video games for 30 minutes, Buelow and colleagues (2015) observed an increase in some executive functions but no increase in risk-taking behavior in the BART. Other researchers observed an association between a history of playing reckless-driving or other risk-glorifying games and risky driving (e.g., Fischer et al, 2007;Stollberg & Lange, 2020) or risky behaviors such as smoking, aggression, or delinquency (e.g., Hull et al, 2014), respectively. However, some of these findings are disputed (see Hilgard et al, 2019;Drummond et al, 2021).…”
Section: The Special Case Of Esportsmentioning
confidence: 99%
“…Video games can be divided into enormous genres through a huge diversity of potential experiences which contains considerably slow-moving and hard strategy games (i.e., wherein participants have sufficient time to make a careful plan and decision) and fighting games (i.e., where gamers must always make judgments and respond as quickly as they can). According to earlier studies, playing racing games can encourage participants to engage in unsafe driving practices, and increase players' risk-taking [2]. Another research has shown that aggressive behavior and cognition can be significantly improved through playing violent video games [3].…”
Section: Introductionmentioning
confidence: 99%